COVID-19-Related Anosmia: The Olfactory Pathway Hypothesis and Early Intervention - Gori, Alessandra; Leone, Fabrizio; Loffredo, Lorenzo; Cinicola, Bianca Laura; Brindisi, Giulia; De Castro, Giovanna; Spalice, Alberto; Duse, Marzia; Zicari, Anna Maria (Frontiers in Neurology, 2020)
Anosmia is a well described symptom of Corona Virus Disease 2019. Several respiratory viruses are able to cause post-viral olfactory dysfunction, suggesting a sensorineural damage. Since the olfactory bulb is considered an immunological organ contributing to prevent the invasion of viruses, it couldhave a role in host defence. . The inflammatory products locally released in COVID-19, leading to a local damage and causing olfactory loss, simultaneously may interfere with the viral spread into the central nervous system. In this context, olfactory receptors could play a role as alternative way of SARS-COV2 entry into cells locally, in the Central Nervous System and systemically. Differences in Olfactory Bulb due to sex and age may contribute to clarify the different susceptibility to infection and understand the role of age in transmission and disease severity. Finally, evaluation of the degree of functional impairment (grading), central/peripheral anosmia (localization) and the temporal course (evolution) may be useful tools to counteract COVID-19.